2013
DOI: 10.1038/bjc.2013.347
|View full text |Cite
|
Sign up to set email alerts
|

NGR-TNF, a novel vascular-targeting agent, does not induce cytokine recruitment of proangiogenic bone marrow-derived cells

Abstract: Background:Administration of certain chemotherapy drugs at the maximum tolerated dose, vascular-disrupting agents (VDAs) and irradiation can induce mobilisation and tumour homing of proangiogenic bone marrow-derived cells (BMDCs). Increases in cytokines and chemokines contribute to such mobilisation that eventually promotes tumour (re)growth. NGR-TNF is a vascular-targeting agent in advanced clinical development, coupling the CNGRCG angiogenic vessel-homing peptide with tumour necrosis factor-alpha (TNF). We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Preparation and characterization of NGR-mTNF was previously described. 25 NGR-mTNF was administered intraperitoneally (i.p.) at 5 pg/gr per mouse once or three times a week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation and characterization of NGR-mTNF was previously described. 25 NGR-mTNF was administered intraperitoneally (i.p.) at 5 pg/gr per mouse once or three times a week.…”
Section: Methodsmentioning
confidence: 99%
“…Since it has been demonstrated that NGR-mTNF induces apoptosis of tumor and endothelial cells in vivo, 25 we evaluated the number of apoptotic cells in angiogenic islets after the last treatment, by immunofluorescence microscopy with anti-cleaved-caspase3 mAb. 25 As expected, we observed a significant increase of apoptotic cells (Fig. S1).…”
Section: Ngr-mtnf Treatment Controls the Development Of Angiogenic Ismentioning
confidence: 99%
“…Glufosfamide has also proved effective against soft-tissue sarcomas, for which it progressed into Phase II trials (NCT00441467) 174,175 ; however, its development for this indication seems to have been halted. The NGR (Asn-Gly-Arg) peptide ligand which targets aminopeptidase N (a cell surface receptor that is overexpressed in many cancers), is also undergoing evaluation as a conjugate with tumour necrosis factor-α for treatment of solid tumours (NCT00483093) 176,177 . Low-density lipoprotein receptor-related protein 1 (LRP1), a cell surface receptor that is involved in cancer metastasis, has been successfully targeted by a small-molecule drug conjugate that consists of three molecules of paclitaxel linked to the homing peptide, angiopep 2 (REF.…”
Section: Mip-1072mentioning
confidence: 99%
“…Both these immunocytokines are being investigated and show promising antitumour and antiangiogenic activity in advanced melanoma. As an antitumour agent, TNF has major toxicity in the endothelial cells of the tumour-associated vasculature and increases the antitumour immune response 109 110. A prospective, uncontrolled multicentre phase II trial in Italy (EudraCT #2012-001991-13) is testing the efficacy and safety of an intratumorally administered combination of L19-IL2 plus L19-TNF in patients with advanced metastatic melanoma.…”
Section: The Current State Of Antiangiogenic Therapies In Melanomamentioning
confidence: 99%
“…A prospective, uncontrolled multicentre phase II trial in Italy (EudraCT #2012-001991-13) is testing the efficacy and safety of an intratumorally administered combination of L19-IL2 plus L19-TNF in patients with advanced metastatic melanoma. The study is ongoing, and its results are not yet available 110. Another vasculature-targeting agent being investigated in melanoma is NGR-TNF, which is generated by the fusion of the CNGRCG peptide to the N-terminal domain of human TNF 111.…”
Section: The Current State Of Antiangiogenic Therapies In Melanomamentioning
confidence: 99%